The Experience and Religiosity toward Tourist Satisfaction: The Case of Umrah Pilgrimage - Nanggong, Ardiwansyah; Hiola, Putra Reski; Pakaya, Syaiful (Universitas Pendidikan Indonesia, 2022)
ABSTRACTThe study of tourism and pilgrimage is still less prominent in Indonesia amid the large potential market segment in this business. The main purpose of this study to explore the effect of experience and religiosity on the satisfaction of pilgrims in religious tourism since the impact of religious tourism can vary based on level of religious experience of adherents. The quantitative approach conducted through distributing questionnaires to 125 people who are Umrah pilgrims. The study findings show a significant role of experience and religiosity to increase pilgrim satisfaction on the journey of Umrah. This study also highlights the implications in the context of religious tourism that the role of personal values and tourist behavior is very substantial. Motivation that is spiritually has a bigger impact than emotional experiences in fulfilling the expectations of pilgrims on religious sites. The results study indicates necessary matters in creating satisfaction in religious tourism while still combining profane and spiritual aspects.ABSTRAKStudi pariwisata dan ziarah masih kurang menonjol di Indonesia ditengah besarnya segmen pasar potensial dalam bisnis ini. Tujuan utama studi ini untuk mengeksplorasi efek pengalaman dan religiusitas pada kepuasan peziarah wisata religi karena dampak wisata religi dapat bervariasi berdasarkan pengalaman religiusitas pemeluknya. Pendekatan kuantitatif digunakan melalui penyebaran kuesioner pada 125 jamaah umroh. Temuan studi menunjukkan peran signifikan dari pengalaman dan religiusitas untuk meningkatkan kepuasan peziarah dalam perjalanan ibadah umroh. Studi ini juga menyorot implikasi pada konteks wisata religi bahwa peran personal values dan tourist behavior sangat substansial. Motivasi yang bersifat spritual berdampak lebih besar dibanding pengalaman emosional dalam memenuhi harapan yang diinginkan peziarah pada situs religi. Hasil penelitian mengindikasikan hal-hal yang diperlukan dalam menciptakan kepuasan pada wisata religi dengan tetap memadukan aspek profan dan spiritual.